2021
DOI: 10.1039/d1ob01642c
|View full text |Cite
|
Sign up to set email alerts
|

PhI(OAc)2-mediated trifluoromethylthiolation/oxidative cyclization of ynamides

Abstract: A PhI(OAc)2-mediated trifluoromethylthiolation/oxidative cyclization of ynamides with Shen reagent has been established herein, providing a facile access to CF3S-substituted oxazolidine-2,4-diones bearing a quaternary carbon center in 38~85% yields with chemo-selectivities...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The desired products bearing a quaternary carbon centre were obtained in 38–85% yields with chemoselectivities of up to 99/1 (Scheme 59). 118…”
Section: Synthesis and Functionalisation Of Heterocycles Using Hyperv...mentioning
confidence: 99%
See 1 more Smart Citation
“…The desired products bearing a quaternary carbon centre were obtained in 38–85% yields with chemoselectivities of up to 99/1 (Scheme 59). 118…”
Section: Synthesis and Functionalisation Of Heterocycles Using Hyperv...mentioning
confidence: 99%
“…The desired products bearing a quaternary carbon centre were obtained in 38-85% yields with chemoselectivities of up to 99/1 (Scheme 59). 118 In the proposed mechanism, the electrophilic addition of CF 3 S + to alkynamide (93)…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…Eosin Y was used to carry out the metal-free visible light organo-photoredox activation of PIDA by Yadav et al, and this was employed for the conversion of arylboronic acids (163) to phenols (164) (Scheme 57). [137] The optimized reaction parame- All the reactions went forward effectively with substrates that had electron-donating, electron-withdrawing, and halogen-containing groups.…”
Section: Chemistryselectmentioning
confidence: 99%
“…Using sodium sulfinates and PIDA, a very effective metalfree decarboxylative sulfonylation methodology was developed by Kuhakarn et al for the production of (E)-vinylsulfones (240) from β-aryl-α,β-unsaturated carboxylic acids (238). [163] This method allowed for the quick and easy synthesis of (E)vinylsulfones with a wide range of functional groups (Scheme 83). It was suggested that this decarboxylative sulfonylation reaction followed a radical-based route.The optimized reaction parameters are: 238(1 equiv.…”
Section: C-hetero Bond Formationmentioning
confidence: 99%